Adsorption of Anionic Reactive Dyes from Solution by Activated Carbon: Effect of Solution pH - S. Al-Degs, Yahya; I. El-Barghouthi, Musa; A. Khraisheh, Majeda (Asian Journal of Chemistry, 2010)
The influence of pH on reactive dyes adsorption from solution is studied in this paper. The adsorbent used was flltrasorb 400 (FS-400) which showed a high equilibrium capacity for hardly adsorbable reactive dyes. The adsorption performance of FS-400 was not affected over a wide pH range (3-10), hence FS-400 is considered as a pH-insensitive adsorbent. Hydrolysed reactive dyes, the state at which reactive dyes are usually discharged, were effectively adsorbed by FS-400. Capacities ranging from 20-80% by weight of FS-400 have been realized.